Walking-friendly built environments and objectively measured physical function in older adults - Mohammad Javad Koohsari; Gavin R. McCormack; Tomoki Nakaya; Ai Shibata; Kaori Ishii; Akitomo Yasunaga; Yung Liao; Koichiro Oka (Elsevier, 2020)
Background: Few studies have examined the associations between urban design attributes and older adults' physical function. Especially, it is not well known how built-environment attributes may influence physical function in Asian cities. The aim of this study was to examine associations between objectively measured environmental attributes of walkability and objectively assessed physical function in a sample of Japanese older adults. Methods: Cross-sectional data collected in 2013 from 314 older residents (aged 65-84 years) living in Japan were used. Physical function was estimated from objectively measured upper- and lower-body function, mobility, and balance by a trained research team member. A comprehensive list of built-environment attributes, including population density, availability of destinations, intersection density, and distance to the nearest public transport station, were objectively calculated. Walk Score as a composite measure of neighborhood walkability was also obtained. Results: Among men, higher population density, availability of destinations, and intersection density were significantly associated with better physical function performance (1-legged stance with eyes open). Higher Walk Score was also marginally associated with better physical function performance (1-legged stance with eyes open). None of the environmental attributes were associated with physical function in elderly women. Conclusion: Our findings indicate that environmental attributes of walkability are associated with the physical function of elderly men in the context of Asia. Walking-friendly neighborhoods can not only promote older adults' active behaviors but can also support their physical function.